Building Character on the Road to Emmaus: Lukan Characterization in Contemporary Literary Perspective - Dinkler, Michal Beth (Journal of Biblical literature, 2017)
Despite the recent spate of scholarly publications related to characterization in New Testament narratives, no consensus has been reached. Scholars cannot agree on whether Luke's Jesus is characterized primarily as a teacher, as the Messiah, or as a rival to Caesar. Neither can scholars agree on whether Luke's disciples are flat paradigms of positive or negative behavior or on whether Luke liberates, oppresses, or sends double messages about women, the poor, and those who need healing. Some read Luke's religious and political authorities as uniformly negative stock characters, while others contend that they are more nuanced and complex. Contemporary theorists of characterization outside of biblical studies have focused on different questions from those typically asked by New Testament scholars. I contend that literary theorists' proposed solutions to their questions can profitably shift our considerations of characterization in New Testament narratives. This article proceeds in three movements. First, I sketch several trends in New Testament studies of characterization. Second, I describe three theoretical premises shared by many contemporary literary theorists regarding characterization. Finally, I consider how taking these literary-theoretical orientations as points of departure can shift the terms of our discussions of New Testament characterization. The illustrative text throughout is Luke 24:13-35, in which the risen Jesus meets the disciple Cleopas and his anonymous companion on the road to Emmaus.